A Fit Model of Organizational Leadership (Journal of Organizational Psychology, 2020)
Leadership theory has been historically separated along paradigmatic lines. Each paradigm has evolved toward a situational model, as researchers uncovered moderating influences on proposed leadership processes. The author examines this trend, and then proposes a meso-model of organizational leadership based on fit theory. Fit theory is an interactional view of organizational relationships based on similarity and exchange between entities. The proposed fit theory of leadership offers a lens through which leadership can be viewed which implicitly captures the situational and hierarchical nature of leadership processes, while allowing for the integration of extant leadership theory.
Keywords: Organizational Psychology; leadership; fit theory; exchange theory; meso-model; Organizational Leadership